Enterprise security risk management : concepts and applilcations - Allen, Brian J.; Loyear, Rachelle (Rothstein Publishing, 2018)
Showing you how ESRM applies fundamental risk principles to manage all security risks, this step-by-step book includes realistic case studies, questions to help you assess your own security program, thought-provoking discussion questions, and useful figures and tables. --